A method for producing 16Cr ferritic stainless steel for flux-cored welding wire and slab thereof
Through the electric furnace-AOD converter-LF refining furnace process, the chemical composition and austenite potential of 16Cr ferrite stainless steel are controlled, and electromagnetic stirring and nanotitanium refining agent are used to solve the problems of high C, N, and P content and poor deep-drawing performance in the existing 16Cr ferrite stainless steel, and high-performance production of stainless steel for flux-core welding wire is achieved.
Patent Information
- Application Number
- CN202310367910.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-07
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-04-07
AI Technical Summary
The existing 16Cr ferrite stainless steel has high C, N and P content, which cannot meet the composition requirements of flux-core welding wire, and its deep drawing performance and fracture problems during the drawing process are difficult to solve.
Steel is smelted through the electric furnace-AOD converter-LF refining furnace process, and the chemical composition and austenite potential of 16Cr ferrite stainless steel are controlled, and electromagnetic stirring and nanotitanium refining agent are used to reduce grain size and improve plasticity.
The C, N and P contents are reduced, the deep-drawing performance of 16Cr ferrite stainless steel is improved, the martensite content in the slab is reduced, the occurrence of crack defects is avoided, and the purity and thickness specification requirements of stainless steel for flux-core welding wire is met.
Smart Images

Figure CN116288040B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of stainless steel smelting, and in particular to a production method of 16Cr ferrite stainless steel for flux-cored welding wire. Background Art
[0002] Stainless steel flux-cored welding wire is mainly used in special shipbuilding and petrochemical equipment industries. Its preparation process is: stainless steel thin strip is rolled into a round or special-shaped steel pipe, filled with a certain amount of powder and then drawn. Among them, 16Cr ferritic stainless steel can produce 410 series stainless steel flux-cored welding wire, which is mainly used for wear-resistant surfacing, such as roller repair, mining equipment repair, etc.
[0003] Ordinary 16Cr ferritic stainless steel cannot meet the composition requirements of flux-cored welding wire due to its high C, N, and P content. In addition, the stainless steel used for flux-cored welding wire is a thin product below 0.4mm. The inclusions and deep drawing performance of ordinary 16Cr ferritic stainless steel cannot meet the requirements, and it is easy to break during the drawing process, polluting the production site. Summary of the invention
[0004] The purpose of the present invention is to provide a method for producing 16Cr ferritic stainless steel for flux-cored welding wire and its slab in view of the technical problem that the content and preparation process of existing 16Cr ferritic stainless steel cannot meet the use requirements of flux-cored welding wire.
[0005] To achieve its purpose, the present invention adopts the following technical solution:
[0006] A 16Cr ferritic stainless steel for flux-cored welding wire, whose chemical composition is calculated by weight percentage as follows: C: 0.020-0.030%, Si: 0.30-0.40%, Mn: 0.30-0.40%, P≤0.025%, S≤0.005%, Cr: 16.00-16.20%, N: 0.025-0.035%, and the rest is Fe and unavoidable impurities.
[0007] As a preferred embodiment of the technical solution of the present invention, the austenite potential of the 16Cr ferritic stainless steel is controlled at 22.65-31.10, and the austenite potential calculation formula is: (189+470×N%+420×C%+7×Mn%)-(11.5×Cr%+11.5×Si%).
[0008] The above 16Cr ferritic stainless steel can be used to prepare 16Cr ferritic stainless steel slabs for flux-cored welding wires.
[0009] The production method of the slab made of 16Cr ferritic stainless steel for the above-mentioned flux-cored welding wire comprises the following steps:
[0010] a. Smelting: Molten steel is smelted through the process of electric furnace-AOD converter-LF refining furnace, among which,
[0011] The electric furnace melts 400 series scrap steel, and the weight ratio of scrap steel to coke is 20:1. The chemical composition after smelting in the electric furnace is C: ≥1.8%, Si: ≥0.2%, Mn: ≥0.15%, P≤0.025%, S≤0.04%, Cr: 14.00~15.00%, and the rest is Fe and unavoidable impurities; the scrap steel composition is: C: 0.03~0.05%, Si: ≤0.40%, Mn: ≤0.40%, P≤0.025%, S≤0.005%, Cr: 16.00~16.40%, N: ≤0.05%, and the rest is Fe and unavoidable impurities.
[0012] The AOD converter smelting goes through decarburization and reduction stages. The decarburization stage is based on the target composition, and ferrochrome is added for chromium alloying. The amount of ferrochrome added is 20-30kg / ton of steel. Ferrosilicon is used in the reduction stage, and the basicity of the reducing slag is 1.6-1.8. The slag is poured after AOD reduction, and the slag thickness is 300-400mm. The chemical composition after AOD smelting is C: 0.015-0.025%, Si: 0.30-0.40%, Mn: 0.30-0.40%, P≤0.025%, S≤0.005%, Cr: 16.00-16.20%, N: 0.025-0.035%, and the rest is Fe and unavoidable impurities.
[0013] After the LF refining station is charged, slag is melted by electricity, and MgO and SiO are added. 2 To adjust the slag basicity, MgO addition amount is 50-100kg / ton steel, SiO 2 Addition amount: 30-50kg / ton steel, slag basicity: 1.4-1.6;
[0014] The chemical composition of molten steel after LF refining is C: 0.020~0.030%, Si: 0.30~0.40%, Mn: 0.30~0.40%, P≤0.025%, S≤0.005%, Cr: 16.00~16.20%, N: 0.025~0.035%, and the rest is Fe and unavoidable impurities;
[0015] b. Continuous casting: pour the molten steel in step a into a tundish, control the tundish temperature to 1520°C to 1530°C, apply electromagnetic stirring, the electromagnetic stirring current intensity is 1700A, and cast the molten steel into a slab.
[0016] Furthermore, in step b, before casting, a refiner is added to the tundish in advance, and the amount of the refiner added is 2.0-3.0 kg / ton of steel.
[0017] Further, the refiner composition is: 3.5% of nano titanium, the rest is Fe and inevitable impurities;
[0018] The beneficial effects of the present invention are:
[0019] 1. The 16Cr ferritic stainless steel provided by the present invention has reduced C, N and P contents, meeting the use requirements of ferritic stainless steel for flux-cored welding wires. Low C and N contents are beneficial to improving the deep drawing performance of the 16Cr ferritic stainless steel.
[0020] 2. The 16Cr ferritic stainless steel provided by the present invention controls the austenite potential within 22.65-31.10, which can reduce the martensite content in the slab and avoid the generation of crack defects.
[0021] 3. The present invention reduces the grain size of the slab by controlling the temperature of the tundish at 1520-1530°C and applying high-intensity electromagnetic stirring.
[0022] 4. The present invention makes the refiner evenly distributed in the molten steel through the impact stirring effect of molten steel injected into the tundish, and the nano-titanium induces ferrite nucleation, reduces the grain size of the slab, and improves the plasticity and toughness.
[0023] 5. The smelting process of the present invention uses low-basicity slag to plasticize inclusions and meet the purity requirements of stainless steel liquid for flux-cored welding wire with a thickness of less than 0.4 mm. LF refining adds MgO and SiO 2 To adjust the slag basicity, MgO can protect the furnace lining and reduce erosion. 2 It can reduce the basicity of AOD slag and is easy to operate.
[0024] 6. The present invention adopts 400 series self-produced scrap steel for smelting, and the scrap steel ratio reaches more than 90%, which is a green and environmentally friendly production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a product picture of 16Cr ferritic stainless steel slab for flux-cored welding wire produced by the method of Example 1;
[0026] Figure 2 This is a product picture of 16Cr ferritic stainless steel slab for flux-cored welding wire produced by the method of Example 2;
[0027] Figure 3 This is a product picture of 16Cr ferritic stainless steel slab for flux-cored welding wire produced by the method of Example 3. DETAILED DESCRIPTION
[0028] The present invention is described in detail below with reference to specific embodiments.
[0029] Example 1
[0030] The present invention provides a 16Cr ferritic stainless steel for flux-cored welding wire, the chemical composition of which is C: 0.020%, Si: 0.40%, Mn: 0.30%, P: 0.025%, S: 0.005%, Cr: 16.20%, N: 0.025%, and the rest is Fe and unavoidable impurities. The austenite potential of the 16Cr ferritic stainless steel is controlled at 22.65.
[0031] A method for producing a 16Cr ferritic stainless steel slab for flux-cored welding wire comprises the following steps:
[0032] a. Smelting: Molten steel is smelted through the process of electric furnace-AOD converter-LF refining furnace. Among them, the electric furnace melts 400 series self-produced scrap steel, containing C: 0.03%, Si: 0.40%, Mn: 0.40%, P: 0.025%, S: 0.005%, Cr: 16.00%, N: 0.05%, and the rest are Fe and inevitable impurities. The amount of scrap steel added is 100 tons, and the amount of coke added is 5 tons. The chemical composition after electric furnace smelting is C: 1.8%, Si: 0.2%, Mn: 0.15%, P 0.025%, S 0.04%, Cr: 14.00%, and the rest are Fe and inevitable impurities. After the decarburization and reduction stages of AOD converter smelting, the amount of ferrochrome added is 30kg / ton of steel. Ferrosilicon is used for reduction, the basicity of the reduction slag is 1.6, the slag is poured after AOD reduction, and the slag thickness is 400mm; the chemical composition after AOD smelting is C: 0.015%, Si: 0.40%, Mn: 0.30%, P 0.025%, S 0.005%, Cr: 16.20%, N: 0.025%, and the rest is Fe and unavoidable impurities. The LF refining station is electrified to slag, and MgO and SiO are added. 2 To adjust the slag basicity, MgO is added in an amount of 100 kg / ton steel, SiO 2 The addition amount is 50kg / ton steel, and the slag basicity is 1.6. The chemical composition of the molten steel after LF refining is C: 0.020%, Si: 0.40%, Mn: 0.30%, P: 0.025%, S: 0.005%, Cr: 16.20%, N: 0.025%, and the rest is Fe and unavoidable impurities.
[0033] b. Continuous casting: Cast the molten steel in step a into a tundish, control the tundish temperature to 1530°C, apply electromagnetic stirring, and the electromagnetic stirring current intensity is 1700A; cast the molten steel into a slab. Add a refiner to the tundish in advance before casting, the amount of refiner added is 3.0kg / ton of steel, and the refiner composition is: 3.5% nano titanium, and the rest is Fe and unavoidable impurities.
[0034] The mechanical properties and product photos of the 16Cr ferritic stainless steel cold-rolled coil for flux-cored welding wire produced by this embodiment are shown in Tables 1 and Figure 1 shown.
[0035] Example 2
[0036] The present invention provides a 16Cr ferritic stainless steel for flux-cored welding wire, the chemical composition of which is C: 0.030%, Si: 0.30%, Mn: 0.40%, P: 0.023%, S: 0.004%, Cr: 16.00%, N: 0.035%, and the rest is Fe and unavoidable impurities. The austenite potential of the 16Cr ferritic stainless steel is controlled at 31.1.
[0037] A method for producing a 16Cr ferritic stainless steel slab for flux-cored welding wire comprises the following steps:
[0038] a. Smelting: Molten steel is smelted through the process of electric furnace-AOD converter-LF refining furnace. Among them, the electric furnace melts 400 series self-produced scrap steel, and the scrap steel composition is: C: 0.05%, Si: 0.35%, Mn: 0.36%, P: 0.023%, S: 0.004%, Cr: 16.40%, N: 0.041%, and the rest is Fe and inevitable impurities. The amount of scrap steel added is 100 tons, and the amount of coke added is 5 tons. The chemical composition after electric furnace smelting is C: 2.04%, Si: 0.26%, Mn: 0.17%, P 0.023%, S 0.029%, Cr: 15.00%, and the rest is Fe and inevitable impurities. AOD converter smelting goes through decarburization and reduction stages. The decarburization level is based on the target composition, and the amount of ferrochrome added is 20kg / ton of steel. Ferrosilicon is used for reduction, the basicity of the reduction slag is 1.8, the slag is poured after AOD reduction, and the slag thickness is 300mm; the chemical composition after AOD smelting is C: 0.025%, Si: 0.30%, Mn: 0.40%, P 0.023%, S 0.004%, Cr: 16.00%, N: 0.035%, and the rest is Fe and unavoidable impurities. The LF refining station is electrified to slag, and MgO and SiO are added. 2 To adjust the slag basicity, MgO is added in an amount of 50kg / ton steel, SiO 2 The addition amount is 30kg / ton steel, and the slag basicity is 1.6. The chemical composition of the molten steel after LF refining is C: 0.020%, Si: 0.40%, Mn: 0.30%, P: 0.025%, S: 0.005%, Cr: 16.20%, N: 0.025%, and the rest is Fe and unavoidable impurities.
[0039] b. Continuous casting: Cast the molten steel in step a into a tundish, control the tundish temperature to 1520°C, apply electromagnetic stirring, and the electromagnetic stirring current intensity is 1700A; cast the molten steel into a slab. Add a refiner to the tundish before casting, the amount of the refiner added is 2.0kg / ton of steel, and the refiner composition is: 3.5% nano titanium, and the rest is Fe and unavoidable impurities.
[0040] The mechanical properties and product photos of the 16Cr ferritic stainless steel cold-rolled coil for flux-cored welding wire produced by this embodiment are shown in Tables 1 and Figure 2 shown.
[0041] Example 3
[0042] The present invention provides a 16Cr ferritic stainless steel for flux-cored welding wire, the chemical composition of which is C: 0.026%, Si: 0.33%, Mn: 0.36%, P: 0.024%, S: 0.0035%, Cr: 16.12%, N: 0.031%, and the rest is Fe and unavoidable impurities. The austenite potential of the 16Cr ferritic stainless steel is controlled at 27.84.
[0043] A method for producing a 16Cr ferritic stainless steel slab for flux-cored welding wire comprises the following steps:
[0044] a. Smelting: Molten steel is smelted through the process of electric furnace-AOD converter-LF refining furnace. Among them, the electric furnace melts 400 series self-produced scrap steel, and the scrap steel composition is: C: 0.04%, Si: 0.31%, Mn: 0.29%, P: 0.021%, S: 0.0035%, Cr: 16.15%, N: 0.048%, and the rest is Fe and inevitable impurities. The amount of scrap steel added is 100 tons, and the amount of coke added is 5 tons. The chemical composition after electric furnace smelting is C: 2.46%, Si: 0.25%, Mn: 0.21%, P 0.024%, S 0.032%, Cr: 14.2%, and the rest is Fe and inevitable impurities. AOD converter smelting goes through decarburization and reduction stages. The decarburization level is based on the target composition, and the amount of ferrochrome added is 18kg / ton of steel. Ferrosilicon is used for reduction, the basicity of the reduction slag is 1.7, the slag is poured after AOD reduction, and the slag thickness is 350mm; the chemical composition after AOD smelting is C: 0.023%, Si: 0.33%, Mn: 0.36%, P: 0.024%, S: 0.0035%, Cr: 16.12%, N: 0.031%, and the rest is Fe and unavoidable impurities. The LF refining station is electrified to slag, and MgO and SiO are added. 2 To adjust the slag basicity, MgO is added in an amount of 60kg / ton steel, SiO 2The addition amount is 40kg / ton steel, and the slag basicity is 1.5. The chemical composition of the molten steel after LF refining is C: 0.026%, Si: 0.33%, Mn: 0.36%, P: 0.024%, S: 0.0035%, Cr: 16.12%, N: 0.031%, and the rest is Fe and unavoidable impurities.
[0045] b. Continuous casting: Cast the molten steel in step a into a tundish, control the tundish temperature to 1524°C, apply electromagnetic stirring, and the electromagnetic stirring current intensity is 1700A; cast the molten steel into a slab. Add a refiner to the tundish before casting, the amount of the refiner added is 2.5kg / ton of steel, and the refiner composition is: 3.5% nano titanium, and the rest is Fe and unavoidable impurities.
[0046] The mechanical properties and surface photos of 16Cr ferritic stainless steel cold rolled coil for flux cored welding wire are shown in Table 1 and Figure 3 shown.
[0047] Table 1 Mechanical properties of 16Cr ferritic stainless steel cold rolled coil for flux-cored welding wire
[0048]
Claims
1. A 16Cr ferritic stainless steel for flux-cored welding wire, characterized in that: Its chemical composition is calculated by weight percentage as follows: C: 0.020~0.030%, Si: 0.30~0.40%, Mn: 0.30~0.40%, P≤0.025%, S≤0.005%, Cr: 16.00~16.20%, N: 0.025~0.035%, and the rest is Fe and unavoidable impurities; The austenite potential of the 16Cr ferritic stainless steel is controlled at 22.65-31.10, and the austenite potential calculation formula is: (189+470×N%+420×C%+7×Mn%)-(11.5×Cr%+11.5×Si%).
2. A 16Cr ferritic stainless steel slab for flux-cored welding wire, characterized in that: It is made of the 16Cr ferrite stainless steel as claimed in claim 1.
3. The method for producing a slab made of 16Cr ferritic stainless steel for flux-cored welding wire according to claim 2, characterized in that: The steps include: a. Smelting: Molten steel is smelted through the process of electric furnace-AOD converter-LF refining furnace, among which, The electric furnace melts 400 series scrap steel, and the weight ratio of scrap steel to coke is 20:
1. The chemical composition after smelting in the electric furnace is C: ≥1.8%, Si: ≥0.2%, Mn: ≥0.15%, P≤0.025%, S≤0.04%, Cr: 14.00-15.00%, and the rest is Fe and unavoidable impurities; the scrap steel composition is: C: 0.03-0.05%, Si: ≤0.40%, Mn: ≤0.40%, P≤0.025%, S≤0.005%, Cr: 16.00-16.40%, N: ≤0.05%, and the rest is Fe and unavoidable impurities; The AOD converter smelting goes through decarburization and reduction stages. The decarburization stage is based on the target composition, and ferrochrome is added for chromium alloying. The amount of ferrochrome added is 20-30kg / ton of steel. Ferrosilicon is used in the reduction stage, and the basicity of the reducing slag is 1.6-1.
8. After AOD reduction, the slag is poured, and the slag thickness is 300-400mm. The chemical composition after AOD smelting is C: 0.015-0.025%, Si: 0.30-0.40%, Mn: 0.30-0.40%, P≤0.025%, S≤0.005%, Cr: 16.00-16.20%, N: 0.025-0.035%, and the rest is Fe and unavoidable impurities. After the LF refining enters the station, it is electrified to slag, and MgO and SiO2 are added to adjust the slag basicity, the amount of MgO added is 50-100kg / ton of steel, the amount of SiO2 added is 30-50kg / ton of steel, and the slag basicity is 1.4-1.6; The chemical composition of molten steel after LF refining is C: 0.020~0.030%, Si: 0.30~0.40%, Mn: 0.30~0.40%, P≤0.025%, S≤0.005%, Cr: 16.00~16.20%, N: 0.025~0.035%, and the rest is Fe and unavoidable impurities; b. Continuous casting: pour the molten steel in step a into a tundish, control the tundish temperature to 1520°C to 1530°C, apply electromagnetic stirring, the electromagnetic stirring current intensity is 1700A, and cast the molten steel into a slab.
4. The method for producing a slab made of 16Cr ferritic stainless steel for flux-cored welding wire according to claim 3, characterized in that: In step b, before casting, a refiner is added to the tundish in advance, and the amount of the refiner added is 2.0-3.0 kg / ton of steel.
5. The method for producing a slab made of 16Cr ferritic stainless steel for flux-cored welding wire according to claim 4, characterized in that: The refiner components are: 3.5% nano titanium, the rest are Fe and inevitable impurities.
Citation Information
Patent Citations
Medium chromium ferrite stainless steel smelting method capable of improving polishing performance
CN107201425A